Neurovirulence of four encephalitogenic dengue 3 virus strains isolated in Malaysia (1992-1994) is not attributed to their envelope protein - Fong, M.Y.; Yusup, R.; Yusof, R.; Lam, S.K. (2004)
The amino acid sequences of the envelope (E) protein of four encephalitogenic and five non-encephalitogenic dengue 3 virus strains isolated in Malaysia were determined and compared. Multiple sequence alignment revealed a high degree of similarity in the E protein of the strains suggesting that neurovirulence of these four encephalitogenic strains is not attributed to this protein. (C) 2004 Royal society of Tropical Medicine and Hygiene. Published by Elsevier Ltd. All rights reserved.